2017
DOI: 10.1557/mrc.2017.82
|View full text |Cite
|
Sign up to set email alerts
|

Spheroid three-dimensional culture enhances Notch signaling in cardiac progenitor cells

Abstract: Cardiac progenitor cells (CPCs) are a promising candidate for cardiac regeneration, and the interaction between CPCs and their microenvironment can influence their regenerative response. Notch signaling plays a key role in cell fate decisions in the developing and adult heart. Here, we investigated the effect of three-dimensional (3D) spheroid culture, as a model of the 3D microenvironment, on Notch in fetal and adult human CPCs, under room air (20%) and physiological (5%) oxygen tension. Notch signaling is en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…For instance, FAK-associated pathways, typically initiated from cellular interactions with neural ECM molecules such as laminin, play an essential role in the neurogenesis of stem cells. However, such beneficial FAK pathways are often suppressed due to the dominating cell-cell interactions in neurospheres, resulting in less controlled differentiation of stem cells (51)(52)(53)(54)(55)(56)(57). In this regard, we verified that SMART neurospheres, incorporating 3D cell-matrix interactions, induced significantly higher expression of FAK compared to control spheroids (Fig.…”
Section: Smart Neurospheres Generated By Controlled 3d Smart Assemblysupporting
confidence: 55%
“…For instance, FAK-associated pathways, typically initiated from cellular interactions with neural ECM molecules such as laminin, play an essential role in the neurogenesis of stem cells. However, such beneficial FAK pathways are often suppressed due to the dominating cell-cell interactions in neurospheres, resulting in less controlled differentiation of stem cells (51)(52)(53)(54)(55)(56)(57). In this regard, we verified that SMART neurospheres, incorporating 3D cell-matrix interactions, induced significantly higher expression of FAK compared to control spheroids (Fig.…”
Section: Smart Neurospheres Generated By Controlled 3d Smart Assemblysupporting
confidence: 55%
“…It is reported that cardiac cells grown in 3D spheroids have increased NOTCH signaling. 51 Marconi et al also highlight the role of NOTCH signaling on cellular behavior and inter-cellular communication within organoids. 52 Hence, down-regulated NOTCH signaling possibly leads to the limited growth ability of WU-225 in 3D culture.…”
Section: Discussionmentioning
confidence: 99%
“…The findings indicate an increase in Notch signaling activation in the 3D spheroid culture due to the in vivo-like microenvironment (Figure 2g). Under hypoxia conditions, fetal CPCs spheroids showed an increased expression in all Notch components and Hey1 (Figure 2h), whereas adult CPCs spheroids displayed upregulation in Notch1, Notch3, and Hey 1 when compared to the respective monolayer culture [84]. Enhancement of Notch signaling is achieved under hypoxia conditions due to the 3D environment and cell-ECM interactions.…”
Section: Spheroidsmentioning
confidence: 95%
“…Spheroids are another 3D cell culture technique of creating an in vivo-like microenvironment by providing multicellular cell-cell and cell-ECM interactions [18]. The Notch signaling pathways of Notch1, Notch2, Notch3, Jag1, and Hey1 were studied in the spheroid culture of human CPCs, which include both adult and fetal human CPCs from adult and fetal human hearts, respectively, under normoxia and hypoxia conditions [84]. Under normoxia, the fetal CPCs spheroids showed upregulation of Notch2, Notch3, Jag1, and Hey 1 compared with a 2D monolayer culture, whereas adult CPCs spheroids displayed upregulation of Notch1, Notch3, and Hey 1.…”
Section: Spheroidsmentioning
confidence: 99%
See 1 more Smart Citation